Association between multimorbidity and quality of life among older adults in community-dwelling of Uttar Pradesh, India - ., Himanshu; Arokiasamy, P.; Selvamani, Y. (International Journal Of Community Medicine And Public Health, 2022)
Background: Increasing longevity with the coexistence of chronic multimorbidity makes the elderly population vulnerable to functional limitation, disability and more frequent hospitalization, resulting deterioration in the quality of life (QoL). The present study examines the association between chronic multimorbidity and QoL among the older population in Varanasi, India. Methods: A cross-sectional data of 500 individuals in the Varanasi district of Uttar Pradesh, India aged 50+ years were collected using a multistage simple random sampling procedure from November 2017 to May 2018. Multimorbidity variable was generated using eight self-reported chronic conditions. WHOQOL-BREF was utilised to assess the QoL of the study participants. Descriptive analysis was performed to assess the mean QoL score pattern, whereas multivariate linear regression analysis examines the association between multimorbidity and QoL. Results: The mean age of respondents was 64 [±10.7] years, and 49% were female. Eighteen percent of study participants had multimorbidity (2+). The mean QoL score was 70, which decreased with age and was found higher among males (73). Multivariable regression analysis shows that demographic and lifestyle risk factors are significantly associated with QoL. Elderly with multimorbidity (β=-4.42; 95% CI=-7.18: -1.66) and physical inactivity (β=-4.65; 95% CI=-6.9: -2.3) was significantly associated with reduced QoL. Conclusions: Multimorbidity along with demographic and lifestyle factors are significantly associated with QoL. Healthcare programmes need to focus multimorbidity while promoting healthy and risk-free lifestyle to control modifiable risk factors. For their day-to-day needs, government assistance is necessary for the most economically dependent older population.